Developing a Desktop-Based OSI Model Interactive Learning Application Using VB.NET - Syahputra, Fahmy; Putri, Tansa Trisna Astono; Mardhiyah, Hanifah; Saragi, Frans Jhonatan; Rahmi, Alya (CV. Rayyan Dwi Bharata, 2024)
This research focuses on developing a desktop-based learning application to help students understand the concept of OSI Model using VB.NET. The purpose of this application is to provide interactive learning media that can facilitate understanding of the seven layers of OSI and the process of data transmission in the network. This research applies the Waterfall method, starting from requirements analysis, system design, implementation, testing, to the operation and maintenance stage. The development results show that this application is equipped with structured learning material features, evaluation quizzes, and user-friendly navigation. The application trial shows performance in accordance with the design, where the quiz evaluation feature is able to provide an accurate assessment of student understanding. In conclusion, this learning application can be an innovative solution in the delivery of OSI Model material, with further development opportunities that include the addition of interactive simulations and support for mobile devices.